Preliminary Analysis of Denial-Of-Service Attack for a Power Constrained Networked Control System - Acosta-Barbosa, K (Institute of Electrical and Electronics Engineers Inc., 2024)
In this work, we consider the preliminary analysis of cyber attacks, in the form of Denial-of-Service (DoS) attacks, on a power constrained Networked Control System (NCS). For insight into the proposed analysis we limit the study to first order plant models, but this is without loss of generality in the context of a NCS, and more so, it is in line with a Networked Process Control System (NPCS) which call to focus only on the dominant dynamics of the process to be controlled. The DoS attack is modelled as a Bernoulli process that can take place either at the sender or the receiver side of the communication channel. For the communication channel model we consider here the standard additive white noise (AWN) channel. For the proposed setup, we then analyze the stability of the resulting feedback loop, characterized in terms of the interference resulting from the DoS attack. © 2024 IEEE.